Dynamic modeling and simulation of tailing thickener units for the development of control strategies. (15th January 2019) - Langlois, Juan I.; Cipriano, Aldo
Highlights: We accomplish a consistent and tractable numerical simulation of the thickening process. The simulation includes the transport of a dynamic particle size distribution. The simulation includes the thickeners underflow yield stress as an output variable. The simulator can be used in the study of multivariable control strategies. Abstract: The purpose of this paper is to extend existing mathematical models of tailings rheology and sedimentation to form a complete dynamic simulator. It is complete in the sense that it includes all important rheological variables for the development of multivariable control strategies and can be integrated with other stages of tailings management systems. This work extends a one-dimensional model for the dynamics of a flocculated suspension in a clarifier-thickener to include the discharge yield stress and particle size distribution in a manner that is computationally tractable. The paper also extends a static yield stress model to include the effect of particle size distribution, in a manner that is consistent with previous empirical and theoretical evidence. The dynamic simulator is validated through the simulation of a Proportional-Integral control strategy and proves to be a useful and flexible tool for the development of control strategies.